Identifying Collaboration Skills Through Discovery Learning with A Contextual Approach - Elsima Nainggolan; Dyah Purwaningsih (Postgraduate, University of Mataram, 2024)
Passive learning results in low student collaboration skills and tends to be individualistic in chemistry. Discovery learning with a contextual approach is one solution to overcome this problem. This research aims to find out the improvement of students' collaboration skills through discovery learning with a contextual approach and can be one step to prepare students' adaptive collaboration skills in the future. This research is quantitative research with a sample of 69 students taken using random sampling technique. Data were collected using collaboration skills observation sheets, questionnaires, and interviews. The collaboration skills measured consist of 4 indicators, namely cooperation skills, communication skills, completing tasks, and commitment. Data analysis uses quantitative descriptive methods. The results of this research show that students' collaboration skills using discovery learning with a contextual approach increase at each meeting with an average of 79 collaboration skills (good category).